IMPLEMENTASI METODE GASING TERHADAP KEMAMPUAN PEMAHAMAN KONSEP FISIKA SISWA SMAN 1 LAKUDO - rusliadi; Azhar A. (Lembaga Pengembangan Kinerja Dosen, 2022)
Research has been carried out on the implementation of the gasing method on the ability to understand students' physics concepts where before the gasing method was implemented into the learning process, physics subjects did not receive a positive response from students and still considered that physics mostly had formulas that had to be memorized, as well as symbols and calculations used. quite complicated for students. Those are some of the factors that cause physics learning to be less than optimal which can be seen from the lack of understanding of students' physics concepts on the material. To overcome this problem, the top method is implemented in learning which can create a fun and enjoyable learning atmosphere in the teaching and learning process. This method can also help explain a natural phenomenon that cannot be witnessed or studied directly. Based on the results of research that has been carried out, students who are taught using the gasing method have a better understanding of physics concepts, namely 67.65% with a variance of 6.08 compared to students who are taught by conventional methods of 54.84% with a variance of 5.26.